Willingness to bear adversity and beliefs about the curability of advanced cancer in older adults. Issue 14 (28th March 2019) - Loh, Kah Poh; Mohile, Supriya G.; Epstein, Ronald M.; McHugh, Colin; Flannery, Marie; Culakova, Eva; Lei, Lianlian; Wells, Megan; Gilmore, Nikesha; Babu, Dilip; Whitehead, Mary I.; Dale, William; et al.
Abstract : Background: Older patients with advanced cancer who are 100% certain they will be cured pose unique challenges for clinical decision making, but to the authors' knowledge, the prevalence and correlates of absolute certainty about curability (ACC) are unknown. Methods: Cross‐sectional data were collected in a geriatric assessment trial. ACC was assessed by asking patients, "What do you believe are the chances that your cancer will go away and never come back with treatment?" Response options were 100% (coded as ACC), >50%, 50/50, <50%, 0%, and uncertain. The willingness to bear adversity in exchange for longevity was assessed by asking patients to consider trade‐offs between survival and 2 clinical outcomes that varied in abstractness: 1) maintaining quality of life (QOL; an abstract outcome); and 2) specific treatment‐related toxicities (eg, nausea/vomiting, worsening memory). Logistic regression was used to assess the independent associations between willingness to bear adversity and ACC. Results: Of the 524 patients aged 70 to 96 years, approximately 5.3% reported that there was a 100% chance that their cancer would be cured (ACC). ACC was not found to be significantly associated with willingness to bear treatment‐related toxicities, but was more common among patients who were willing to trade QOL for survival (adjusted odds ratio, 4.08; 95% CI, 1.17‐14.26). Conclusions: Patients who were more willing to bear adversity in the form of an abstract state, namely decreased QOL, were more likely to demonstrate ACC. Although conversations regarding prognosis should be conducted with all patients, those who are willing to trade QOL for survival may especially benefit from conversations that focus on values and emotions. Abstract : Patients who were more willing to bear adversity in the form of an abstract state, decreased quality of life, were more likely to believe, with 100% certainty, that they could be cured. Although conversations regarding prognosis should be conducted with all patients, those who are willing to trade quality of life for survival may especially benefit from conversations that focus on values and emotions.